ANALISIS PERAN PADA LINGKUNGAN SOSIAL DAN BUDAYA TERHADAP PEMASARAN GLOBAL - Suhairi, Suhairi; Nasution, Amanda Damayanti; Putri, Helva Diansyah; Hutapea, Miftahul Husna; Hutasuhut, Muhammad Anshari (Bussman Journal : Indonesian Journal of Business and Management, 2023)
The study uses the method of literature study or literature review. Literature review is a comprehensive overview of the research that has been done on a specific topic to show the reader what is known about the topic and what is not known, to seek rationale for research that has been done or for ideas for further research. The type of writing used is a literature review study that focuses on writing results related to writing topics or variables. The author conducts this literature study after determining the topic of writing and establishing the formulation of the problem, before going into the field to collect the necessary data. Any systematic study of a new market geography requires a combination of sober minds and generosity. But marketers also have to feel secure in their own beliefs and traditions. Generosity is needed to maintain whole values ??and other ways of life and other values ??based on other people's perspectives. in other words, overcoming the negative prejudices that are a natural result of human tendencies toward ethnocentrism. Although "culture shock" is a normal human reaction to something new and unknown, successful global marketers strive to understand the human experience of life from a local point of view